Format Conjunction in the Syriac language (Mark's Gospel as a Model): A Contrastive Semitic Linguistic Study - Fadel, Abeer Ghalib; Jassem, Ashwaq Nusrat (Al-Adab Journal, 2023)
The subject of our study is format conjunction in the Syriac language (Mark's Gospel as a model), a contrastive Semitic linguistic study.Conjunction is the subjunctive that one of the conjunctions mediates between it and what follows it; or it is the link between two sentences or a clause by means of a conjunction.What is conjunction? How many conjunction words are there? Is there a difference in the number of these words? And what are its rules? In order to answer these questions, it is called conjunction because it coordinates texts or speech so that the coordinated noun takes the form of the preceding noun according to certain rules. The conjunctions are ( Al-Waw-and, Al-Fa-and, thuma-then , Aw-or, Am-or, La-nor, Hata-till, Bal-but, Lakin-but, Ama-or). There is a difference between the Arabic language and Syriac language in the number of conjunctions.There are a number of rules which govern the use of conjunctions, like coordinating two verbs or two sentences.The limits of the research is in the Gospel of Mark, an applied study, following a contrastive approach for Semitic languages such as Syriac, Hebrew and Arabic.The present study concluded the following results:The sources of conjunctions in the Arabic language are numerous and in Semitic languages as well, but some studies have approached conjunctions as e dependents, so this study is considered very important in the field of Syriac language and its comparison with the Hebrew and Arabic languages. Despite the difference between Arab and Syriac grammarians in the number of conjunctions, the researcher agrees with the majority of grammarians in the number.